The Relationship between Knowledge and Stress Levels Facing Premenstrual Syndrome in Class X Female Students at SMK Swasta Alwasliyah 17 - Pohan, Rostina Afrida; Meni Fuzi Astuty Tanjung; Erlina Esther Rotua Siringoringo (International Journal of Public Health Excellence (IJPHE), 2023)
Premenstrual Syndrome (PMS) Is a group of physical, behavioral and emotional symptoms that occur cyclically and repeatedly Around 75% of women complain of symptoms of premenstrual syndrome and 30% of them require treatment. This study aims to identify the relationship between knowledge and stress levels in dealing with pre-menstrual syndrome in class X female students at SMK Swasta Alwasliyah 17, Air Putih District. This type of research is correlational, namely examining the relationship between two variables in a situation or group of subjects, using a cross-sectional approach, namely looking for the relationship between the variables studied. The place of this research was carried out at SMK Swasta Alwasliyah 17, Air Putih District, Batubara Regency. The sample for this research was 30 female students in class X of SMK Swasta Alwasliyah 17. Based on statistical tests, it is known that there is a relationship between the level of knowledge and the level of stress in dealing with pre-menstrual syndrome, characterized by a significance value of p-value 0.000 > (0.05) where the p-value is 0.000 and the chi-square value is 48.302. Suggestions in research so that teenagers can increase their knowledge about pre-menstrual syndrome and control excessive stress by learning relaxation techniques to minimize stress.